2014
DOI: 10.1080/10476210.2014.957666
|View full text |Cite
|
Sign up to set email alerts
|

Does student teaching matter? Investigating pre-service teachers’ sense of efficacy and preparedness

Abstract: The purpose of this study was to investigate how student teaching experiences impact the sense of teaching efficacy and feelings of preparedness of pre-service teachers in a nearly and elementary teacher education program (EC-6). The study used an action research, mixed-methods design. Seventy-one pre-service teachers at a large public university in the southwest completed surveys about their preparedness to teach and teaching efficacy pre and post the student teaching semester. Findings indicate that pre-serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 53 publications
(71 reference statements)
10
58
0
8
Order By: Relevance
“…Different types of professional experience models have been associated with PSTs' levels of TSE, but the results are mixed because of such things as different designs of teaching practice and practice environments. For example, school-based professional experience and microteaching can increase PSTs' levels of TSE (Brown, Lee, & Collins, 2014) for certain aspects such as instructional strategies (Tuchman & Isaacs, 2011), but have also been found to decrease TSE (Plourde, 2002) or to have no impact at all (Atay, 2007). Key factors appear to include opportunities to participate in the design of professional experience activities, receiving constructive feedback, and modelling the instructors' teaching (Cinici, 2016).…”
Section: The Role Of Teacher Education Programsmentioning
confidence: 99%
“…Different types of professional experience models have been associated with PSTs' levels of TSE, but the results are mixed because of such things as different designs of teaching practice and practice environments. For example, school-based professional experience and microteaching can increase PSTs' levels of TSE (Brown, Lee, & Collins, 2014) for certain aspects such as instructional strategies (Tuchman & Isaacs, 2011), but have also been found to decrease TSE (Plourde, 2002) or to have no impact at all (Atay, 2007). Key factors appear to include opportunities to participate in the design of professional experience activities, receiving constructive feedback, and modelling the instructors' teaching (Cinici, 2016).…”
Section: The Role Of Teacher Education Programsmentioning
confidence: 99%
“…A pre-service teacher (PST) typically experiences student teaching just prior to graduation from his or her teacher preparation program. Student teaching has long served as a culminating experience in the preparation of a PST and is an important experience to help PSTs prepare for their own classrooms (Brown, Lee, & Collins, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies put forth that perceived teacher self-efficacy has a significant effect on attitudes and behaviors towards teaching and teachers' competencies. For example, perceived teacher efficacy and thus their readiness for teaching is an important indication on how well they will confront the problems in their profession (Brown, Lee & Collins, 2015).…”
Section: Perceived Teacher Self-efficacymentioning
confidence: 99%
“…Programs should celebrate and praise students' successful experiences in certification exams (Petchauer, 2016). Brown et al (2015) found that candidates' self-efficacy prior to entering the program improved after they completed their studies. In other words, teacher training programs had an effect on self-efficacy.…”
Section: Perceived Teacher Self-efficacymentioning
confidence: 99%